The CAADP inaugural Biennial Review and Africa Agricultural Transformation Scorecard: Results and areas for improvement - Benin, Samuel; Ulimwengu, John M.; Tefera, Wondwosen (International Food Policy Research Institute, 2018)
This paper uses the Biennial Review (BR) data and simple correlations to analyze the potential relationship between progress in recommitting to CAADP or mutual accountability and progress in meeting commitments in the other five broad areas. Various weighting systems are used to demonstrate the sensitivity of the weights chosen for computing the scores to develop the Africa Agricultural Transformation Scorecard (AATS). The current BR applies equal weights to the seven thematic areas, followed by equal weights to performance categories and indicators within each thematic area and performance category, respectively. The other weighting systems considered for the sensitivity analysis include equal weights applied at performance category or indicator level, differential weights based on the ease or difficulty in achieving various commitments using the Items Response Theory (IRT), and differential weighting system that gives more weight to performance categories or indicators that are more directly linked to agricultural transformation.